6z+3=17-z

Simple and best practice solution for 6z+3=17-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z+3=17-z equation:


Simplifying
6z + 3 = 17 + -1z

Reorder the terms:
3 + 6z = 17 + -1z

Solving
3 + 6z = 17 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
3 + 6z + z = 17 + -1z + z

Combine like terms: 6z + z = 7z
3 + 7z = 17 + -1z + z

Combine like terms: -1z + z = 0
3 + 7z = 17 + 0
3 + 7z = 17

Add '-3' to each side of the equation.
3 + -3 + 7z = 17 + -3

Combine like terms: 3 + -3 = 0
0 + 7z = 17 + -3
7z = 17 + -3

Combine like terms: 17 + -3 = 14
7z = 14

Divide each side by '7'.
z = 2

Simplifying
z = 2

See similar equations:

| o(n)=2(5)-1 | | -13+x=32 | | 4y+9y+8y+5= | | 17y-13+6y^2-14y+5= | | 5(x^2)+15x=e^4 | | C=30+0.7Y | | 28(2x-1)=7(x+3)2x | | 2+4(x-1)=5-8(x-7) | | 28(2x-1)=7(x+3)22x | | -2x+63=-49+6x | | 76=15.7xh^2 | | 10-x=65 | | 2x+27=2x-11 | | 4b+-8=2b+6-4b+13 | | 0=-16t^2+0t+64 | | n+0.6+n=n+0.1+2n | | 7.5+1x=2.5x | | Y/12=17/13 | | 12x+(30-2x)+12x=144 | | 7x+5x-6=2x+6 | | 62735/628358=x | | 15=5(n-8) | | log(7)(6x-5)=2 | | 4x-21=x+21 | | 17+x=-8 | | 72+19362/56=x | | 9/10 | | -15=x+20 | | 6x+5=x | | t/16=30/36 | | 5(x+1)+6(x+6)=60 | | -2w^2-5w-52=0 |

Equations solver categories